Nitrogen and potassium fertilization affects banana production (Research, Society and Development, 2020)
Banana crop presents rapid growth and high fruit production, demanding intense fertilization, with nitrogen and potassium being the most outstanding nutrients. However, national productivity is still low, indicating the need for studies to improve the performance of this fruit. Thus, the objective of this work was to evaluate the productivity and fruit characteristics of Thap Maeo banana, second cycle, under nitrogen and potassium fertilization. Plants of the cultivar Thap Maeo were used in spacing of 2.5 m x 2.5 m. The experimental design was in randomized blocks in a 2 x 4 factorial scheme with three replicates. The combination of presence (400 kg ha-1) or absence of nitrogen and four doses of potassium (0, 300, 600 and 900 kg of K2O ha-1) composed the treatments. It was observed that the application of K2O at the best doses gave gains of 8.5; 5.9; 16.3; 50.2; 20.0 and 27.6%, respectively, for the hands per bunch, fruits per hand, fruits per bunch, fruit diameter and fruit length, and fruit yield, when compared to the control. It was concluded that the use of nitrogen in association with K2O influences in isolation the number of hands per bunch and fruits per bunch, increasing their values. The variables hands per bunch, fruits per hand, fruits per bunch, fruit diameter, length and yield were benefited by the application of K2O, and the best doses were in the range of 502.7 to 658.0 kg ha-1.